2021
DOI: 10.1002/fsn3.2341
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic browning in relation to permeation of oxygen into the kernel of postharvest areca nut under different storage temperatures

Abstract: Previous study indicates that kernel of areca nut is susceptible to enzymatic browning caused by phenolic oxidation, which involves the ingression of oxygen into interior tissue. However, the reason for permeation of oxygen into the interior of areca nut and its possible influencing factors (e.g., temperatures) are little known. In the present study, we set three storage temperatures (25, 10, and 5°C) and investigated the effects on kernel browning and related physic‐biochemical and tissue morphological change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…This showed that the cocoa pod tissue did not undergo significant morphological changes at 30 °C. The results obtained were similar to studies on the storage of areca nuts (Pan et al, 2021), reporting that between temperature variations of 5, 10, and 25 °C, the storage temperature of 10 °C did not cause significant morphological changes in areca nuts, while at 25 and 5 °C, lignification occurred in the areca bean mesocarp tissue. An increase in lignin content was caused by natural aging and cold stress, respectively.…”
Section: Hardness and Moisture Content Of Cocoa Pod Husksupporting
confidence: 87%
“…This showed that the cocoa pod tissue did not undergo significant morphological changes at 30 °C. The results obtained were similar to studies on the storage of areca nuts (Pan et al, 2021), reporting that between temperature variations of 5, 10, and 25 °C, the storage temperature of 10 °C did not cause significant morphological changes in areca nuts, while at 25 and 5 °C, lignification occurred in the areca bean mesocarp tissue. An increase in lignin content was caused by natural aging and cold stress, respectively.…”
Section: Hardness and Moisture Content Of Cocoa Pod Husksupporting
confidence: 87%
“…However, as a tropical fruit, the betel nut can experience a chilling injury when stored below 14 • C [83]. Storage at 25 or 5 • C increased polyphenol oxidase (PPO) activity and reduced the total phenolic content in the kernel [86]. Another study has shown that a storage temperature of 10 • C was better than 4 • C [87].…”
Section: Cold Storage and Chilling-injury-prevention Technologymentioning
confidence: 99%
“…Mounting evidence suggests that sustained accumulation of ROS is the main factor that causes postharvest endocarp browning of longan fruit. Excessive amounts of ROS accelerate lipid peroxidation in membranes, resulting in the breakdown of cell structure and the following disruption of enzyme-substrate compartmentalization, which allows the interaction between polyphenol oxidases (PPOs) that located in cytoplasm and their phenolic substrates from vacuoles (Pan et al 2021;Yan et al 2022). The browning reactions are then triggered, PPOs catalyze continuous oxidation steps and form redox-active quinones, which subsequently react with amino acids, polyphenols, and proteins, and converted into brown polymers, melanin (Zhang et al 2021).…”
Section: Introductionmentioning
confidence: 99%